Production of instant ‘nasi lemak’ flavour ingredient from palm olein - Omar, Muhammad Nor; Ibrahim , Noni Suhaila; Anvarali, Mohamed Nazim; Desa, Zaidi Mat (Malaysian Agricultural Research and Development Institute, 2002)
Instant ‘nasi lemak’ flavour ingredient was prepared by microencapsulation of palm olein and pandan leaf flavour. The pandan-flavoured encapsulated powder was obtained after spray drying using maltodextrin (DE15) and sodium caseinate as wall materials. Analysis of the encapsulated powder indicated that the moisture, oil and surface oil content were 2.17%, 68.1% and 20.5% respectively. Gas chromatographic analysis revealed that 78.57% pandan flavour was encapsulated in the powder.